The 3Ps: A tool for coach observation - Taylor, Jamie; MacNamara, Áine; Collins, Dave (Frontiers in Sports and Active Living, 2023)
There is growing recognition of the value of “in situ” coach development practice across a variety sporting contexts. Unfortunately, however, there remains a limited number of tools available with which to observe coaching practice. In this study, we pilot and test a quasi-systematic tool for observation in the form of the 3Ps. Drawing on a range of representational perspectives, the theoretically neutral labels of “procedure”, “planning”, and “process” were developed for the purpose of holistic observation. In order to test the tool, a group of experienced coach development practitioners (n = 10) integrated the tool into their practice over a 12-month programme of professional development. Those participants subsequently took part in semi-structured interviews, in which they expressed a strong sense of acceptability, perceiving effectiveness and positive opportunity cost. We propose that the 3Ps tool presents a holistic and practically useful means of observing coaches’ professional judgment and decision making. We also suggest future directions for the researcher who seeks to generate evidence in a naturalistic coaching context.